Structural Modification of Organic Thin-Film Transistors for Photosensor Application - Jeong, Hyeon Seok; Bae, Jin-Hyuk; Lee, Hyeonju; Ndikumana, Joel; Park, Jaehoon (Journal of the Korean Physical Society, 2018)
We investigated the light response characteristics of bottom-gate/top-contact organic TFTs fabricated using pentacene and polystyrene as an organic semiconductor and a polymeric insulator, respectively. The pentacene TFT with overlaps (50 μm) between the source and gate electrodes as well as between the drain and gate electrodes exhibited negligible hysteresis in its transfer characteristics upon reversal of the gate voltage sweep direction. When the TFTs were structurally modified to produce an underlap structure between the source and gate electrodes, clockwise hysteresis and a drain-current decrease were observed, which were further augmented by increasing the gate underlap (from 30 μm to 50 μm and 70 μm). Herein, these results are explained in terms of space charge formation and accumulation capacitance reduction. Importantly, we found that space charges formed under the source electrode contributed to the drain currents via light irradiation through the underlap region. Under constant bias conditions, the TFTs with gate underlap structures thus exhibited on-state drain current changes in response to light signals. In our study, an optimal photosensitivity exceeding 11 was achieved by the TFT with a 30 μm gate underlap. Consequently, we suggest that gate underlap structure modification is a viable means of implementing light responsiveness in organic TFTs.